TAFSIR ILMI TENTANG PENCIPTAAN MANUSIA DALAM TAFSIR AL-JAWAHIR KARYA THANTHAWI JAWHARI - Muhammad Nasir; Asep Nana Sonjaya; Kerwanto (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2024)
In response to this interpretation of science, there are two groups of scholars: opposers and supporters. In fact, many contemporary scholars are more moderate in responding to the interpretation of "knowledge" because the scientific theories are not the final form of interpretation or the Qur'an is not the book of science but the Book of guidance and mercy for human life. There is an attempt to justify that the Qur'an contains all knowledge, religion and general. This article aims to analyze the history of the emergence of the scientific interpretation, methods and approaches, the description of the intellectual interpretation of the process of human creation by Thanthawî. The research is carried out using methods of library study using sources from books and articles. This article discusses the upcoming cycle of tafsir ilmi beginning in the golden age of Islamic victories in the Abbasid dynasty. Study of the scientific interpretation of the Qur'an by using the methods of tahlîlî and scientific approaches.